Генітивні речення в українській мові - Горпинич, В. (Iнститут української мови НАН України, 2009)
У статті розглянуто проблему генітивного речення в українській мові. Виділено 10 структурних типів цих речень. Доведено, що немає підстав включати генітивні реченняв систему безособових. Однією з суттєвих ознак підмета в генітивних реченнях є йогонезалежність. Пропоновано замінити термін “номінативні речення” на “називні речення”, відповідно до їхньої функції. Genitive sentences problems in Ukrainian language are discussed. There are seprited 10 structural types of such sentences. It is shown there is no reason to include the genitive sentences in the impersonality type of sentences. Independence is the one of the essential attributes of the subject in a genitive sentence. According to their functions the term "nominative sentence" is proposed to replace to "denominative sentence".